(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Peripartum cardiomyopathy (PPCM) is a rare condition associated with the development of acute heart failure (AHF) during the peripartum period, carrying a high maternal mortality rate (6–10% within 6 months). Intensive management of AHF in PPCM requires a comprehensive approach, including pharmacological therapy, hemodynamic monitoring, and, in severe cases, mechanical circulatory support. This article summarizes current data on the epidemiology, pathophysiology, intensive care strategies, and prognosis of AHF in PPCM, with emphasis on statistical findings and clinical guidelines.